Relation of measured brain glucose utilisation and cerebral atrophy in man. Issue 6 (June 1987) - Schlageter, N L; Horwitz, B; Creasey, H; Carson, R; Duara, R; Berg, G W; Rapoport, S I
Abstract : The effect of cerebral atrophy on measured cerebral metabolic rates for glucose (CMRglc), as determined with positron emission tomography (PET), was examined in 49 healthy males aged 21-83 years. Global CMRglc and regional CMRglc for 34 grey matter regions parallel to and from 30 to 80 mm above the inferior orbital meatal (IOM) line were measured under resting conditions, using [18F]-fluorodeoxyglucose and an ECAT II positron emission tomograph. Using a GE 8800 CT/T scanner, slices parallel to and from 30 to 80 mm above the IOM line were analysed for CSF volume. Cerebral atrophy, indicated by increased CSF volume, was correlated significantly with global CMRglc, but accounted for no more than 13% of the variance in the CMRglc measurements. Methods for correcting for inter-subject variation in CSF volume were proposed. Global values for CMRglc, uncorrected or corrected for CSF volume, were found to be age invariant. These findings indicate that (a) cerebral atrophy has a small, but statistically significant effect on CMRglc as measured with PET; (b) CMRglc is age invariant in healthy males.